Dispute Settlement between Telkomsel and Indosat: An Analysis on Competition of Cellular Operator - Mukti Fajar ND; Diana Setiawati; Yati Nurhayati (Faculty of Law, Sriwijaya University, Indonesia, 2019)
Telecommunication advancement has become a central part of human life brought tight competition among cellular operators. On June 2016, there was a case of business competition between Telkomsel and Indosat (the big Three Cellular operators in Indonesia) that conduct monopoly practice and predatory pricing. In Indonesia, there are two Institutions that maintain business telecommunication and business competition namely Indonesian Telecommunication Regulatory Body (BRTI) has mandated by Law number 36 of 1999 and Business Competition Supervisory Commission (KPPU) by Law Number 5 of 1999. The research aims to know how the government regulates on competition of cellular operator in Indonesia and to know the role of Indonesian Telecommunication Regulatory Body (BRTI) and Business Competition Supervisory Commission (KPPU) to settle the cases on competition of cellular operator (Telkomsel and Indosat cases). The study is normative legal research with statute and case approach, by using juridical qualitative approach. The results of this research are, firstly the analysis of regulation regarding on competition of cellular operator. Secondly the analysis of the role of Indonesian Telecommunication Regulatory Body (BRTI) and Business Competition Supervisory Commission (KPPU) to settle the cases on competition of cellular operator (Telkomsel and Indosat cases) that conduct monopoly practice and predatory pricing, regarding with Law Number 36 of 1999 on Telecommunication and Law Number 5 of 1999 on the Prohibition of Monopolistic Practice and Unfair Business Competition.